N Evolution and Physiochemical Structure Changes in Chars during Co-Pyrolysis: Effects of Abundance of Glucose in Fiberboard - Deliang Xu; Liu Yang; Ming Zhao; Yu Song; Karnowo; Hong Zhang; Xun Hu; Hongqi Sun; Shu Zhang (Energies, 2020)
The simple incineration of wood-based panels (WBPs) waste generates a significant amount of NOx, which has led to urgency in developing a new method for treating the N-containing biomass residues. This work aims to examine the N evolution and physiochemical structural changes during the co-pyrolysis of fiberboard and glucose, where the percentage of glucose in the feedstock was varied from 0% to 70%. It was found that N retention in chars was monotonically increased with increasing use of glucose, achieving ~60% N fixation when the glucose accounted for 70% in the mixture. Pyrrole-N (N-5) and Pyridine-N (N-6) were preferentially formed at high ratios of glucose to fiberboard. While the relevant importance of volatile–char interactions to N retention and transformation could be observed, the volatile–volatile reactions from the two feedstocks played a vital role in the increase in abundance of glucose. With the introduction of glucose, the porous structure and porosity in chars from the co-pyrolysis were dramatically altered, whereas the devolatilization of glucose tended to generate larger pores than the fiberboard. The insignificant changes in carbon structure of all chars revealed by Raman spectroscopy would practically allow us to apply the monosaccharides to the WBPs for regulating N evolution without concerns about its side effects for char carbon structures.